HUMBLE BEGINNINGS WITH BIG GOALS: SMALL MOLECULE SOLUBLE EPOXIDE HYDROLASE INHIBITORS FOR TREATING CNS DISORDERS - Zarriello, Sydney (Prog Neurobiol, 2018)
Soluble epoxide hydrolase (sEH) degrades epoxides of fatty acids including epoxyeicosatrienoic acid isomers (EETs), which are produced as metabolites of the cytochrome P450 branch of the arachidonic acid pathway. EETs exert a variety of largely beneficial effects in the context of inflammation and vascular regulation. sEH inhibition is shown to be therapeutic in several cardiovascular and renal disorders, as well as in peripheral analgesia, via the increased availability of anti-inflammatory EETs. The success of sEH inhibitors in peripheral systems suggests their potential in targeting inflammation in the central nervous system (CNS) disorders. Here, we describe the current roles of sEH in the pathology and treatment of CNS disorders such as stroke, traumatic brain injury, Parkinson’s disease, epilepsy, cognitive impairment, dementia and depression. In view of the robust anti-inflammatory effects of stem cells, we also outlined the potency of stem cell treatment and sEH inhibitors as a combination therapy for these CNS disorders. This review highlights the gaps in current knowledge about the pathologic and therapeutic roles of sEH in CNS disorders, which should guide future basic science research towards translational and clinical applications of sEH inhibitors for treatment of neurological diseases.